2001
DOI: 10.1038/35082026
|View full text |Cite
|
Sign up to set email alerts
|

Liquid marbles

Abstract: The transport of a small amount of liquid on a solid is not a simple process, owing to the nature of the contact between the two phases. Setting a liquid droplet in motion requires non-negligible forces (because the contact-angle hysteresis generates a force opposing the motion), and often results in the deposition of liquid behind the drop. Different methods of levitation-electrostatic, electromagnetic, acoustic, or even simpler aerodynamic techniques-have been proposed to avoid this wetting problem, but all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
939
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,036 publications
(972 citation statements)
references
References 19 publications
27
939
1
5
Order By: Relevance
“…Under these conditions the aluminum droplet exhibited a considerably different behavior. As shown in Figure 12, the droplet impinged on the substrate (1 ms), spread (7 ms), and then bounced away from the substrate (13, 25 and reported with the coated water droplets [49]. The authors of this study reported that the wetting of these droplets on glass was suppressed by coating them with a monolayer of hydrophobic powder.…”
Section: Effect Of Gaseous Atmospheresmentioning
confidence: 84%
“…Under these conditions the aluminum droplet exhibited a considerably different behavior. As shown in Figure 12, the droplet impinged on the substrate (1 ms), spread (7 ms), and then bounced away from the substrate (13, 25 and reported with the coated water droplets [49]. The authors of this study reported that the wetting of these droplets on glass was suppressed by coating them with a monolayer of hydrophobic powder.…”
Section: Effect Of Gaseous Atmospheresmentioning
confidence: 84%
“…Configurations promoting non-contact have been explored, e.g. encapsulating the drop by a hydrophobic powder (Aussillous & Quere 2001) or oscillating the liquid surface to periodically renew the air film (Couder et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been shown that drops coated by hydrophobic microparticles, i.e. liquid marbles 15,16 , can also levitate 17 . Moreover, the critical temperature above which the Leidenfrost effect takes place does not exist for liquid marbles, i.e.…”
Section: Introductionmentioning
confidence: 99%